Radically local supply chains through territorial brands: Insights from the 100% Local project - Godina Golija, Maja (Acta geographica Slovenica, 2023)
The modernization of food supply chains has marginalized remote agricultural regions such as the Alps. As a result, local actors often adopt new ways of producing, promoting, and selling their products by differentiating them in the eyes of consumers. The labelling of quality local agri-food products through the development and promotion of territorial brands play an essential role in this respect. In the article we address the research question: What are the conditions for the creation, development and sustainability of territorial brands in the agri-food sector? What are the characteristics of some territorial brands, which are an essential development factor and the subject of local identities and local policies? We discuss cooperation between local, regional, and national actors. The aim of this article is to highlight the preparation and role of the 100% Local Model for the successful creation and development of territorial brands in the field of agro-food production in the Alps.